The impact of a training curriculum to develop speed motor wheelchair tennis players Ground for people with disabilities (Journal of the College of Basic Education, 2022)
Identify the impact of the training curriculum to develop speed motor wheelchair for tennis players Ground disabled, and the researcher experimental method style groups Almtkavitin (experimental and control) with tests pre and post suitability of the nature of the search, and selected sample search as deliberate, as it consisted of (10) players from players elected Iraqi National tennis Ground for the disabled (junior class), as were divided randomly into two groups experimental and control group, each group is composed of (5) players, and after applying the training curriculum prepared by the researcher for a period (8) weeks the number of units (24) and a training module by three units per week and duration of the unit (30) minutes given the exercises move using wheelchairs, researcher reached conclusions that the most important exercises stomach was effective in developing speed motor wheelchair for tennis players Ground disabled, that continuous training and repeated on the development speed motor helped develop defense Ground pitch tennis features.